Living with the enemy: the return of an apex predator is associated with habitat shifts in a common but rapidly declining prey population - Ekblad, Camilla; Lindén, Andreas; Öst, Markus; Below, Antti; Jaatinen, Kim; Lokki, Heikki; Seimola, Tuomas; Tikkanen, Hannu; Laaksonen, Toni (Springer Nature, 2025)
Context The recovery of some apex predators has led to concerns for endangered prey that may have developed risky habitat selection tactics during predator-free eras. Environmental heterogeneity affects predator–prey coexistence, but spatial redistribution of prey has rarely been studied. A predator–prey system with white-tailed eagles and common eiders provides a unique opportunity to study the effect of returning predators on an abundant but declining prey population. Objectives Our objective was to investigate how the physical environment affects predator–prey relationships and subsequently the spatial redistribution of the prey population over time, and to perform a large-scale assessment of the population status and distribution of eiders in the North-Eastern Baltic Sea. Methods Using extensive survey data from the Finnish coast from 1997 to 2020 on predator and prey breeding numbers, we constructed a spatiotemporal model explaining the distribution of eiders on > 3600 islands across highly variable coastal regions. We assessed how the proximity of nesting eagles affected eider abundance, mediated by properties related to physical nest shelter (archipelago type and island forest cover). Results Breeding eider numbers decreased on exposed islands particularly near eagle nests, while they increased near eagle nests in the sheltered archipelago. We observed population-scale predator-induced shifts in the breeding distribution, likely reflecting both excess mortality on exposed islands and a shift of the population core to low-risk habitats. Conclusions We show that a returning predator can affect the distribution and density of its prey in a habitat-specific manner, which is important to consider in parallel with effects of human-induced ecosystem changes during conservation planning.
Keywords: breeding distribution; conservation conflict; habitat selection; predator–prey dynamics; raptor